Effect of potassium and secondary nutrients on the essential oil and oleoresin contents in kacholam (Kaempferia galanga L.) - Kavitha, P.R.; Menon, Meera V (Journal of Tropical Agriculture, 2013)
Kacholam (Kaempferia galanga L.) is an important medicinal and aromatic oil yielding plant of Kerala. A study was conducted in the College of Horticulture, Vellanikkara, to identify the role of secondary elements, viz., sulphur, calcium and magnesium, on the qualitative components of the rhizomes of kacholam. Twelve treatments including the package of practices recommendations for kacholam, and combinations of the same with sulphur, calcium and magnesium were applied in the crop in a randomized block design withy three replications. Top dressing of sulphur and magnesium resulted in higher rhizome yields (8.56 and 8.24 t ha-1). Sulphur application also resulted in higher oleoresin and essential oil contents. Higher sulphur and calcium contents in rhizomes were related to application of these elements. Path co-efficient analysis revealed that the secondary nutrients play a decisive role in the development of oleoresin and essential oil in kacholam.